2017
DOI: 10.1042/bcj20170543
|View full text |Cite
|
Sign up to set email alerts
|

Toward a systems approach to the human cytochrome P450 ensemble: interactions between CYP2D6 and CYP2E1 and their functional consequences

Abstract: Functional cross-talk among human drug-metabolizing cytochromes P450 through their association is a topic of emerging importance. Here we studied the interactions of human CYP2D6, a major metabolizer of psychoactive drugs, with one of the most prevalent human P450 enzymes, ethanol-inducible CYP2E1. Detection of P450-P450 interactions was accomplished through luminescence resonance energy transfer (LRET) between labeled proteins incorporated into human liver microsomes and the microsomes of insect cells contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…The finding that the activation of BQ metabolism and attenuation of its cooperativity may be reproduced in HLM-N samples via incorporation of the exogenous CYP2E1 into their membranes suggests that these effects, at least in a part, represent direct results of the alcohol-induced increase in CYP2E1 content. The striking effects of one P450 protein on the functional properties of another P450 enzyme observed in this study and evidenced in earlier reports from our group and by others (Backes et al, 1998;Kelley et al, 2006;Reed et al, 2010;Davydov et al, 2015;Davydov et al, 2017) may be best explained with a concept of "positional heterogeneity" in P450 oligomers (Davydov, 2011;Davydov et al, 2015;Davydov, 2016;Reed and Backes, 2017;Davydova et al, 2019). This concept is based on considering heteromeric complexes of multiple P450 species as a predominant state of the P450 enzymes in the microsomal membrane.…”
Section: Multifold Activation Of Cyp3a4 By Alcohol Exposure Is Stipulsupporting
confidence: 81%
See 2 more Smart Citations
“…The finding that the activation of BQ metabolism and attenuation of its cooperativity may be reproduced in HLM-N samples via incorporation of the exogenous CYP2E1 into their membranes suggests that these effects, at least in a part, represent direct results of the alcohol-induced increase in CYP2E1 content. The striking effects of one P450 protein on the functional properties of another P450 enzyme observed in this study and evidenced in earlier reports from our group and by others (Backes et al, 1998;Kelley et al, 2006;Reed et al, 2010;Davydov et al, 2015;Davydov et al, 2017) may be best explained with a concept of "positional heterogeneity" in P450 oligomers (Davydov, 2011;Davydov et al, 2015;Davydov, 2016;Reed and Backes, 2017;Davydova et al, 2019). This concept is based on considering heteromeric complexes of multiple P450 species as a predominant state of the P450 enzymes in the microsomal membrane.…”
Section: Multifold Activation Of Cyp3a4 By Alcohol Exposure Is Stipulsupporting
confidence: 81%
“…International, New Brunswick, NJ (Davydov et al, 2017). In the experiments with Cary Eclipse the excitation was performed with a monochromatic light centered at 405 nm with 5 nm bandwidth.…”
Section: Fluorimetric Assays Of Bq Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…recent studies on a large selection of human liver microsomes (HLM) demonstrated the lack of a straight correlation between the composition of human cytochrome P450 ensemble and the profile of drug metabolism [4]. At the same time, there is an emerging recognition of the functional importance of physical interactions between multiple P450 species co-localized in the microsomal membrane [59]. Due to complex effects of these interactions any change in the content of a particular P450 enzyme may affect drug metabolism in a complex, hard-to-predict manner.…”
mentioning
confidence: 99%
“…In our recent study we also explored the interactions between CYP2E1 with CYP2D6 and observed the formation of their heteromeric complexes in microsomal membrane. We demonstrated that these interactions inhibit the activity of CYP2E1, while exerting a time-dependent activating effect on CYP2D6 in the presence of its specific substrates, 3-[2-(N,N-diethyl-N-methyl ammonium)ethyl]-7-methoxy-4-methylcoumarin (AMMC) and bufuralol [9]. Of particular importance might be the effect of CYP2E1 on the stoichiometry of futile cycling and substrate oxidation by CYP2D6 revealed in a decrease in the electron leakage from CYP2D6 through the peroxide-generating pathways [9].…”
mentioning
confidence: 99%